2021
DOI: 10.21037/tp-20-166
|View full text |Cite
|
Sign up to set email alerts
|

Narrative review of the influence of high-intensity interval training on adolescents’ bone health: commentary and perspectives

Abstract: Although several benefits have been associated to high-intensity interval training (HIIT), there is a lack of clarity on the HIIT effects in adolescents, especially on bone health outcomes. To address this gap, our research aimed to perform a systematic review, which focus on the influence of HIIT on adolescents' bone health. Our search strategy was conducted on three databases (PubMed, SCOPUS, and Embase). For our review, we included articles with the following characteristics: (I) sample consisting of adoles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…High-impact exercises, such as resistance-based HIIT, may enhance bone mass accumulation during these crucial developmental years. Yet, there is a dearth of research investigating the association between HIIT and bone health (18). Emerging evidence suggested that both acute and chronic HIIT leads to enhanced cognitive adaptations and brain health (63, 64).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High-impact exercises, such as resistance-based HIIT, may enhance bone mass accumulation during these crucial developmental years. Yet, there is a dearth of research investigating the association between HIIT and bone health (18). Emerging evidence suggested that both acute and chronic HIIT leads to enhanced cognitive adaptations and brain health (63, 64).…”
Section: Discussionmentioning
confidence: 99%
“…Review-based evidence indicates that school-based HIIT interventions effectively enhance body composition (14)(15)(16), CRF (15,16) and muscular health (17). However, the impact on cognitive function and academic performance remains uncertain (15) and evidence regarding its health benefits for mental well-being (15) and bone health (18) is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Although HiInEx proved effective in improving physical fitness [ 75 ], its effect on bone health among school boys and girls remains unclear [ 76 ]. Our study suggested that the BMD of the HiInEx group increased compared with the baseline, but the change was not significant compared with that of the ShEx group.…”
Section: Discussionmentioning
confidence: 99%
“…2 The author' s advice to professional athletes engaged in wrestling training, and the anaerobic power of non-wrestling sports college students, a comparative study was carried out, the change law of anaerobic power in wrestling training under load conditions is discussed, and the method and reference for scientific sports training evaluation and monitoring are provided. 3…”
Section: Introductionmentioning
confidence: 99%